MODEL OF THE RELIABILITY OF LED EMITTING DEVICE IN THE EXTERIOR LIGHTS (Municipal economy of cities (Technical science), 2013)
Proposes a model of reliability of the LED emitting devices and the prospects for further improvement of outdoor lighting of the city.